Karakteristik Sifat Kimia Tanah Dan Status Kesuburan Tanah Lahan Pekarangan Dan Lahan Usaha Tani Beberapa Kampung Di Kabupaten Kutai Barat - Abdul Rahmi; Maya Preva Biantary (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2014)
The purpose of the study was to determine the soil chemical characteristics of the soil and soil fertility status at the home yard and farm lands in several villages of West Kutai District.The experiment was conducted for 3 (three) months, from April 2013 to July 2013 in the villages of Muut and Dempar of Nyuatan Sub District, Purwodadi Village of Linggang Bigung Sub District; Sumber Sari Village of Barong Tongkok Sub District, and Melak Ilir Village of West Kutai District. This study used survey system, followed by soil sampling compositely at a depth of 0-20cm.  The composite soil samples were then analyzed in the laboratory.The main data that were collected include soil pH, organic C, total N, the C/N ratio, available P, cation-exchangeable base cations, CEC, base saturation, and saturation Aluminum.  The data were analyzed using soil chemical status assessment criteria and soil fertility assessment criteria of Bogor Soil Research Center. The results showed that: (1) the character of the soil chemical properties at home yard and farm land at several villages in West Kutai District, namely: soil pH is very acidic to acidic, organic C content is low to high, N total is low to moderate, C/N ratio is moderate to high, available P is very low to moderate, CEC is relatively very low, base cations classified as very low to moderate, and Al saturation is low to very high; and (2) the status of soil chemical fertility in the home yard and farm land at several villages in West Kutai District is classified as very low to low.